Designing and Developing E-Magazine about Indonesian Cultural Concept in Social Studies Learning for Elementary School Students - Septyani, Hannifah Dwi; Mulyati, Tita; Wahyuningsih, Yona (Universitas Tanjungpura, 2023)
The background of this research is optimizing material on cultural diversity, cultural tourism and special food in Indonesia in class IV SD in social studies learning through the digital media e-magazine Anak Bangsa. The use of the Anak Bangsa e-magazine learning media is due to the lack of use of learning media during the teaching and learning process and a decrease in love for preserving culture. This study aims to produce a product in the form of an e-magazine Anak Bangsa learning media on cultural diversity material in Social Studies class IV SD. This research uses the Design and Development method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The instruments used were questionnaires for validating material experts, media experts, and linguists, questionnaires for teacher and student responses, as well as interviews with educators and students. The research produced the product of Anak Bangsa e-magazine learning media with material on cultural diversity in grade IV SD. The results of the recapitulation of the feasibility test through validation by experts namely material experts, media experts, and language experts using a validation questionnaire obtained the category